2020
DOI: 10.21037/tau.2019.11.21
|View full text |Cite
|
Sign up to set email alerts
|

Long-term oncologic outcomes of positive surgical margins following robot-assisted partial nephrectomy

Abstract: Background: Previous reports on positive surgical margin (PSM) after robot-assisted partial nephrectomy (RAPN) have reached inconsistent conclusions as to the impact of a PSM on oncologic outcomes. We sought to determine the effect of PSM on long-term cancer recurrence and survival outcomes. Methods: We queried our renal oncology database for patients having undergone RAPN and compared recurrence-free survival (RFS) and overall survival (OS) between patients with PSM and negative surgical margin (NSM). Kaplan-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…25 Another retrospective study did not show an association between PSM and worse oncologic outcomes in terms of RFS and OS, concluding that a longer and more intense follow up in patients with PSM could be a valuable strategy. 22 This is consistent with the present analysis, as the higher rate of PSM in patients with a PADUA score of 12-13 did not reflect on differences in RFS and OS when compared with the other two groups of PADUA score using the Kaplan-Meier method. Furthermore, only one out of seven patients of the present cohort who experienced a recurrence had PSM (Table S1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…25 Another retrospective study did not show an association between PSM and worse oncologic outcomes in terms of RFS and OS, concluding that a longer and more intense follow up in patients with PSM could be a valuable strategy. 22 This is consistent with the present analysis, as the higher rate of PSM in patients with a PADUA score of 12-13 did not reflect on differences in RFS and OS when compared with the other two groups of PADUA score using the Kaplan-Meier method. Furthermore, only one out of seven patients of the present cohort who experienced a recurrence had PSM (Table S1).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding margin status, a PSM was identified in 10.5% of the specimens with malignancy in final pathology, which is attributed to the significantly higher PSM rate observed in patients with a PADUA score of 12-13 (P = 0.017), whereas the rates of PSM in the PADUA 10 and PADUA 11 groups were comparable to that reported in previous series of RAPN. 22,23 In a multicenter observational study of 399 patients who underwent RAPN for cT1 renal masses, the reported PSM rate was 6.5%; when the results were divided by PADUA classification, the rate of PSM was 11.5% in patients with a high-complexity tumor (PADUA score ≥10). 23 From the oncological standpoint, the effect of PSM in patients treated with PN in recurrence and survival rates is still conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…We extracted data on local recurrence in two groups from 33 studies ( 4 , 6 , 11 15 , 17 23 , 25 30 , 32 38 , 40 – 45 ) including 13473 patients (PSM: 785, NSM: 12688). In 8 studies ( 13 , 14 , 18 21 , 36 , 38 ), the OR value could not be calculated because the number of local recurrence was zero in both the PSM and NSM groups.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies provided comparative data on tumor metastasis between the two groups ( 4 , 6 , 13 – 15 , 17 , 18 , 20 , 25 , 27 , 30 , 33 36 , 38 , 40 – 43 ), including 434 patients in the PSM group and 8298 patients in the NSM group. In 4 studies ( 13 , 14 , 35 , 36 ), the number of metastatic cases in the two groups was zero, and the OR value could not be calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Ninguno de nuestros pacientes con margen quirúrgico positivo presentó recidiva local, metástasis a distancia ni mortalidad específica de cáncer durante el seguimiento. Por lo tanto, nuestros resultados concuerdan con aquellos que indican que el estado y el tamaño del margen no están asociados con la recurrencia (local o distancia) ni con la mortalidad [38][39][40] .…”
Section: Análisis Estadísticounclassified